Efeito da adição de cargas minerais leves na resistência mecânica de grautes para cimentação de poços offshore - Cabral, Kleber Cavalcanti (2011)
The preparation of cement slurries for offshore well cementing involves mixing all solid components to be added to the mixing water on the platform. The aim of this work was to study the formulation of pre-prepared dry mixtures, or grouts, for offshore oilwell cementing. The addition of mineral fillers in the strength of lightweight grouts applied for depths down to 400 m under water depths of 500 m was investigated. Lightweight materials and fine aggregates were selected. For the choice of starting materials, a study of the pozzolanic activity of low-cost fillers such as porcelain tile residue, microsilica and diatomaceous earth was carried out by X-ray diffraction and mechanical strength tests. Hardened grouts containing porcelain tile residue and microsilica depicted high strength at early ages. Based on such preliminary investigation, a study of the mechanical strength of grouts with density 1.74 g/cm3 (14.5 lb/gal) cured initially at 27 °C was performed using cement, microsilica, porcelain tile residue and an anti-foaming agent. The results showed that the mixture containing 7% of porcelain tile residue and 7% of microsilica was the one with the highest compressive strength after curing for 24 hours. This composition was chosen to be studied and adapted for offshore conditions based on testes performed at 4 °C. The grout containing cement, 7% of porcelain tile residue, 7% of active silica and admixtures (CaCl2), anti-foaming and dispersant resulted satisfactory rheology and mechanical strength after curing for 24 hours of curing